Analisis kemampuan berpikir kritis berdasarkan gaya belajar siswa kelas V pada pembelajaran IPAS SD Negeri 10 Kelapa Kampit Belitung Timur - Alfarezi, Alfarezi; Rezkita, Shanta; Murniningsih, Murniningsih (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to: 1) analyze the level of critical thinking ability of fifth grade students based on visual learning style; 2) auditory; 3) kinesthetic. This research uses a qualitative descriptive method. The research subjects came from class V SDN 10 Kelapa Kampit Belitung Timur based on the results of questionnaire data processing with Rasch Model assisted by WinSteps Software, 6 subjects were selected, namely 2 people with visual learning styles, 2 people with auditory learning styles, and 2 people with kinesthetic learning styles. Then the subject was given a test in the form of a written description question, then the answers were analyzed and an interview was conducted. Data analysis techniques by collecting data, data reduction, data presentation, and conclusion drawing. The data collection techniques of this research are test and non-test techniques in the form of learning style questionnaires, critical thinking ability tests, and in-depth interviews on research subjects. The results showed that: 1) students with visual learning styles are able to fulfill 5 indicators of critical thinking ability. Students with visual learning styles are included in the very high level critical thinking category with a percentage of 84% and 92%; 2) students with auditory learning styles are able to fulfill 4 indicators of critical thinking ability. Students with auditory learning styles are included in the high level critical thinking category with a percentage of 76% and 80%; 3) students with kinesthetic learning styles are only able to fulfill 2 indicators of critical thinking ability. Students with kinesthetic learning styles belong to the low-level critical thinking category with a percentage of 32% and 40%.